Controlling Permanent Magnet Polysolenoid Linear Motor Based On the Nature of Voltage Source Inverter Part 1: Two-Phase Voltage Source Inverter in Polysolenoid Motor Control Structure - et. al., Nguyen Hong Quang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Linear motor produces direct linear motion without intermediate mechanisms. It is usually fed by solid-state power supply. In this paper, a two-level voltage source inverter is designed to supply the Polysolenoid linear motor. Hardware solution and control rules of set of solid-state switches are proposed in order to implement voltage vector modulation technique of the inverter. The results are necessary for closed loop control of Polysolenoid linear motor.